Of treason, God and testicles : political masculinities in British and American films of the early Cold War - Starck, Kathleen (Cambridge Scholars Publishing, 2016)
Gender in general, and masculinity in particular, might not be the first associations the mind produces when presented with the subject matter of the Cold War. More likely contenders would be the arms race or the ideological dichotomy of Communism versus Capitalism. However, recent research has established beyond a doubt that the politics and diplomacy of the superpower conflict were not only strongly influenced by beliefs about gender, but simultaneously also generated them. In fact, in a social climate where gender conformity was considered as crucial as ideological conformity, the conflict gave rise to what might be called distinctive "Cold War masculinities." At the same time, the socio-historical context of the Cold War markedly shaped the cinemas of one of the main Cold War players, the United States, and of its close ally, Great Britain. Both film industries produced films overtly or covertly depicting the Cold War, characterised by propaganda, coercion and resistance to varying degrees. Integrating these findings from the fields of masculinity studies and (cultural) Cold War studies, this book analyses in what shape the interplay between widespread political and ideological Cold War convictions and Cold War notions of masculinity found its way onto British and American cinema screens of the early Cold War